Age-related efficacy of Shigella O-specific-polysaccharide conjugates in 1 to 4 year-old Israeli children - Passwell, Justen H. (Vaccine, 2010)
BACKGROUND: Despite its high worldwide morbidity and mortality, there is yet no licensed vaccine for shigellosis. We reported the safety and immunogenicity of Shigella O-specific polysaccharide-protein conjugates in adults and young children and efficacy of Shigella sonnei conjugate in young adults. METHODS: A double-blinded, randomized and vaccine-controlled Phase 3 evaluation of S. sonnei and S. flexneri 2a O-SP–rEPA conjugates, 25 μg, injected IM twice, 6 weeks apart, into healthy 1 to 4 year-olds, is reported. The children were followed for 2 years by telephone every other week and stool cultures were obtained for each episode of acute diarrhea (≥3 loose stools/day or a bloody/mucous stool). Sera were taken randomly from 10% of the participants for IgG anti-LPS and anti-carrier levels. RESULTS: Of the 2799 enrollees, 1433 received S. sonnei and 1366 S. flexneri 2a conjugates; 2699 (96.4%) completed the two-year follow up. Local reactions occurred in ~5% and ~4% had temperatures ≥38.0°C lasting 1-2 days. There were no serious adverse events attributable to the vaccines. Of the 3,295 stool cultures obtained, 125 yielded S. sonnei and 21 S. flexneri 2a. Immunogenicity and efficacy were age-related. The overall efficacy of the S. sonnei conjugate was 27.5%; 71.1% (P=0.043) in the 3-4 year-olds. The numbers for S. flexneri 2a were too few for meaningful analysis. Cross protection by S. flexneri 2a for non-vaccine S. flexneri types was found, but the numbers were too few for statistical significance. There was an age-related rise of vaccine-specific IgG anti-LPS in both groups, peaking at about 10 weeks and declining thereafter, but remaining ≥4 fold higher than in the controls 2 years after the second dose. CONCLUSIONS: Shigella conjugates are safe and immunogenic in 1 to 4 year-olds. The S. sonnei conjugate elicited 71.1% efficacy in the 3 to 4 year-olds and can be predicted to be efficacious in individuals older than 3 years of age. These results urge studies with our improved conjugates.